Peer-correction and Self-correction of Errors in Foreign Language Classes and their Benefit - Zokirov Mukhtorali; Khasanova Ozodakhon; Askarova Shakhnozakhon (SHS Web of Conferences)
Error correction is an important component of every lesson in every subject, but it is of particular significant importance in foreign language classrooms. In traditional lessons, errors can be corrected mostly by teachers. Peer-correction and self-correction in German classes are not widely used. The purpose of this article is to identify the benefits of peer and self-correction of errors. The ways of using messengers in language acquisition are clarified. Using messengers for the purpose of error correction in after-classroom activities is a highly beneficial practice.